Factors associated with levels of physical activity in chronic kidney disease patients undergoing hemodialysis: The role of dialysis versus nondialysis day - Da Costa Rosa, Clara Suemi [UNESP]; Nishimoto, Danilo Yuzo [UNESP]; Freitas, Ismael Forte [UNESP]; Ciolac, Emmanuel Gomes [UNESP]; Monteiro, Henrique Luiz [UNESP] (Human Kinetics, 2017)
Background: Patients on hemodialysis (HD) report lower physical activity (PA) levels. We analyzed factors associated with low levels of PA in patients with chronic kidney disease (CKD) and compared PA on HD day and non-HD. Methods: 79 patients wore an accelerometer and were classifed according to time spent on moderate-to-vigorous PA (MVPA). Demographic data, BMI, comorbidities, clinical status, and health-related quality of life (HRQoL) were checked for association with PA. In addition, PA level was compared between days of HD and non-HD. Results: Accelerometer compliance was 78.5% [33 men and 29 women (53.96 ± 15.71 yrs) were included in analysis]. 35.5% of sample achieved ≥150min/week on MVPA. Lower MVPA was associated with older age (OR = 5.80, 95% CI = 1.11 to 30.19, P = .04), and lower score of physical function HRQoL (OR = 4.33, 95% CI = 1.23 to 15.23, P = .02). In addition, patients spent 9.73% more time on sedentary behavior, 38.9% less on light PA and 74.9% less on MVPA on HD day versus non-HD day. Conclusion: Age and physical function HRQoL were the main factors associated to lower PA levels. In addition, lower time spent on PA during HD day suggest that strategies for increasing physical activity levels during HD day such exercising during HD session could help CKD patients to reach current PA recommendations.
Keywords: Accelerometry; Exercise; Physical activity assessment